Volunteer Roles in Supporting the Smooth Running of the Gaikindo Jakarta Auto Week Event - Mochamad Amboro Alfianto; Awkila Nathanael Odoh; Muhammad Alandra Bestama; Lazia Putri (An International Journal Tourism and Community Review, 2025)
Automotive exhibitions such as GAIKINDO Jakarta Auto Week (GJAW) require various important elements for their success, one of which is the role of volunteers. Volunteers are individuals who voluntarily and selflessly provide their time, energy, and skills to support social, humanitarian, or organizational activities. In the context of GJAW, they play an important role in the smooth running of the event by helping to manage visitors, supporting various activities organized by the organizers and participants, and providing information about the products and promotions offered. They also play a role in organizing the exhibition location and helping visitors to get a better experience during the event. The efficient and organized role of volunteers is one of the factors that supports the smooth running of operations and increases visitor satisfaction in this large-scale event.